2008
DOI: 10.1016/j.apmr.2007.10.045
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Evaluation of Persons With Disabilities: Does a Longitudinal Definition Help Define Who Receives Necessary Care?

Abstract: Objective-To assess, using a longitudinal definition, the impact of disability on a broad range of objective health care quality indicators.Design-Longitudinal cohort study following up with patients over several years. The first 2 interviews, 1 year apart, were used to determine each patient's disability status in activities of daily living (ADLs). Assessment of the health care indicators commenced after the second interview and continued throughout the survey period (an additional 1-3y).Setting-National surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
(20 reference statements)
3
22
0
Order By: Relevance
“…For AMI, payments decline with age and with the mean number of ADL limitations; the results for age are consistent with past research on the relationship between age and aggressiveness of care following AMI (Spencer et al, 2001). The result for ADL limitations further suggests that persons with co-existing conditions and disabilities are less likely to receive aggressive and costly care, results consistent with more general findings that persons with disabilities are less likely to receive necessary care (Chan et al, 2008). There are clearly some important differences in determinants of Medicare spending among the four diseases which serves to emphasize that treatment patterns differ by admitting condition (Sloan et al, 2004).…”
Section: Tablesupporting
confidence: 87%
“…For AMI, payments decline with age and with the mean number of ADL limitations; the results for age are consistent with past research on the relationship between age and aggressiveness of care following AMI (Spencer et al, 2001). The result for ADL limitations further suggests that persons with co-existing conditions and disabilities are less likely to receive aggressive and costly care, results consistent with more general findings that persons with disabilities are less likely to receive necessary care (Chan et al, 2008). There are clearly some important differences in determinants of Medicare spending among the four diseases which serves to emphasize that treatment patterns differ by admitting condition (Sloan et al, 2004).…”
Section: Tablesupporting
confidence: 87%
“…Sociodemographic characteristics included age (65-74, 75-84, and 85 and over 24 ); gender; race/ethnicity (non-Hispanic African American or Black, Hispanic, non-Hispanic White, and other 25 ); education (high school diploma or greater/less than high school diploma 26 ); income (≤$25,000/>$25,000 27 ); supplemental insurance type (Medicare only, Medicare and Medicaid-dual enrollee, private-supplemental, other (i.e., Champus, VA)); living arrangement (lives alone, with spouse, with children, with other relatives or non-relatives, or in a retirement community); and the presence or absence of accessibility features in the home. Health status was captured by self-reported chronic conditions and impairments.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study suggested that disability status was strongly associated with receipt of quality health care in a broad range of diagnostic categories. 19 Unfortunately, the current study did not collect information on the severity of CHD or on in-hospital treatment. Third, disability could be a prognosis factor per se by limiting the ability of disabled subjects to cope when an acute event occurs, making them more likely to die.…”
Section: Discussionmentioning
confidence: 99%